“Our theatre is society”: Perceptions and practices of university-based African Centres of Excellence regarding community engagement and the third mission of higher education - Du Plooy, B.; von Moellendorff, M. (South African Journal of Higher Education, 2024)
In the historical higher education (HE) context of early post-independence Africa, little was done to unpack or critique the dominant notion of African universities as “developmental” and to create workable models for the future. The resultant conflictual role of African universities, caught between the demands of academic excellence, on the one hand, and local demands of development and regional and communal impact, on the other, have not yet been adequately resolved. Conceptually and organisationally, “engagement”, “transfer” and “outreach” activities serve as mechanisms to bridge the divide between the traditional academy and the needs and expectations of societal stakeholders located outside of formal HE structures. This is now often referred to as the third mission (TM) of HE, the first and second missions being teaching and research. In recent years, many of the existing DAAD (German Academic Exchange Service) African Centres of Excellence (ACE) have established partnerships and networks with actors from the political, social and economic sector to increase their relevance and impact in their regions, especially relating to Sustainable Development Goals. Against this backdrop, a qualitative exploratory study was conducted to determine the experiences and perceptions of participating representatives from ten ACE, located in their different and specific regional and societal contexts, about their university-society community engagement (CE) or TM activities. This article reports on the findings of this study, which contributes to the larger aims of identifying long-term synergies and collaboration potential and the development of conceptual models that are scalable. The findings of this study can form an adaptable basis for future TM-CE projects and for possible future research projects about such activities in HE.